A economia socialista não estatista: revisão histórica das diversas propostas de cooperativismo, autogestão e empresas sociais no socialismo não estatal - Kamichi Miyashiro, Manuel Jose (2023)
The present work shows the economic proposal of important representatives of socialism, where the defense for communal property, cooperatives and social enterprises stands out, all framed within a self-management system; thus moving away from a statist economy. In addition, it is evident that Marx was a critic of the State, for which reason he did not defend a state economy, but rather one based on cooperatives connected in a Great Union exemplified in the Paris Commune, and his proposal for a State was a proletarian one, of participatory and democratic type, very far from statist dictatorships that have falsely used his name as a source of inspiration, and that instead of having implanted a socialist model they executed a state capitalism. Finally, the compatibility of social enterprises with the characteristics of socialism is shown, in which the success of the self-managed socialist model of Yugoslavia when it was governed by Josip Broz Tito, an authentically socialist model, where its economy was based in social enterprises and the self-management of their workers, is seen.